Biomarker analysis of cetuximab plus oxaliplatin/leucovorin/5-fluorouracil in first-line metastatic gastric and oesophago-gastric junction cancer: results from a phase II trial of the Arbeitsgemeinschaft Internistische Onkologie (AIO) - Luber, Birgit; Deplazes, Joëlle; Keller, Gisela; Walch, Axel; Rauser, Sandra; Eichmann, Martin; Langer, Rupert; Höfler, Heinz; Hegewisch-Becker, Susanna; Folprecht, Gunnar; Wöll, Ewald; Decker, Thomas; et al. (BMC cancer, 2011)
The activity of the epidermal growth factor receptor (EGFR)-directed monoclonal antibody cetuximab combined with oxaliplatin/leucovorin/5-fluorouracil (FUFOX) was assessed in first-line metastatic gastric and oesophago-gastric junction (OGJ) cancer in a prospective phase II study showing a promising objective tumour response rate of 65% and a low mutation frequency of KRAS (3%). The aim of the correlative tumour tissue studies was to investigate the relationship between EGFR gene copy numbers, activation of the EGFR pathway, expression and mutation of E-cadherin, V600E BRAF mutation and clinical outcome of patients with gastric and OGJ cancer treated with cetuximab combined with FUFOX.